Is Amman Stock Exchange an Indicator of Jordan's Economic Performance? - Alrefai, Ahmed Hussein (International Journal of Economics and Financial Issues, 2019)
There have been great debate in the literature on the impact of stock market on the economic performance, as some believe that higher stock prices increase the wealth of people and stimulate further investment leading to higher consumption and investment, consequently higher GDP. Others cast doubts on the robustness of that view. In Jordan, an emerging market, the Amman Stock Exchange plays a crucial role in the economy as the share of market capitalization to GDP was more than 200% until 2008 but dropped drastically during the economic turbulences after the Arab Spring to reach only 57% in 2018. This study aims to test whether the stock prices in Jordan are to be used as a leading economic indicator. The Correlation between the former and the latter is measured through the statistical method used by Granger (1969). We used quarterly data for real GDP for the period 2000-Q1 till 2018-Q1 as a proxy for economic growth and the weighted average of Amman Stock exchange index as a proxy for stock prices. We found that the optimum time lag to be used was 4 lags and further the null hypothesis of no Granger-causality between lagged stock prices and GDP was rejected at 5%. This means that lagged stock prices in Jordan can cause economic performance. Such findings offer indication on the plausible use of Jordan lagged stock prices as causal factors to economic performance. As such, in an effort to revive the economy, Jordanian government should incentivize investment and stimulus policies targeting Amman's Stock Exchange. Keywords: Amman Stock Exchange, Granger-Causality, Economic Performance. JEL Classifications: O16, G00, N1 DOI: https://doi.org/10.32479/ijefi.9103